2017
DOI: 10.1371/journal.pone.0185531
|View full text |Cite
|
Sign up to set email alerts
|

Chinese college freshmen’s mental health problems and their subsequent help-seeking behaviors: A cohort design (2005-2011)

Abstract: Based on cohort data obtained from 13,085 college freshmen’s (2005 to 2011) SCL-90 (the Symptom Check-List-90) reports and their subsequent 4-year psychological counseling help-seeking records, this study examined the association between college students’ mental health problems and help-seeking behaviors across four college years. Female students’ mental health problems and help-seeking behaviors increased from the 2005 to the 2011 cohorts and no changes emerged for male students across cohorts. Overall, male … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
60
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 32 publications
5
60
1
1
Order By: Relevance
“…On balance, this unmet need is roughly the same for mental disorders as for STB, with only 25–30% of first year college students with a mental disorder/STB receiving any treatment in a given year. Our data confirm previous reports on the use of services among college students, although our estimates on treatment utilization are somewhat on the lower end of what is generally found in the United States (Han et al, ; Hunt & Eisenberg, ), Europe (McLafferty et al, ; Verger et al, ), and Asia (Liu et al, ). Despite the observed unmet need, the presence of mental disorders/STB remains a strong predictor of treatment.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…On balance, this unmet need is roughly the same for mental disorders as for STB, with only 25–30% of first year college students with a mental disorder/STB receiving any treatment in a given year. Our data confirm previous reports on the use of services among college students, although our estimates on treatment utilization are somewhat on the lower end of what is generally found in the United States (Han et al, ; Hunt & Eisenberg, ), Europe (McLafferty et al, ; Verger et al, ), and Asia (Liu et al, ). Despite the observed unmet need, the presence of mental disorders/STB remains a strong predictor of treatment.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, the screening instrument precludes detailed assessments on important socio-demographic predictors (e.g., detailed family situation at time of survey). Fifth, this study is limited to the use of cross-sectional data, adjusting for a limited range of basic socio- Verger et al, 2010), and Asia (Liu et al, 2017). Despite the observed unmet need, the presence of mental disorders/STB remains a strong predictor of treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a meta-analysis, which included 39 studies, reported an overall prevalence of depression among Chinese university students of 23.8% [3]. Although the prevalence of depressive symptoms among college students in these studies differs from that of the general population (37.9% for depressive symptoms) [4], which may be due to the use of different measurement tools, different methodologies, and different appraisal standards, previous studies have also found a general increase in mental health problems in college students [5]. Furthermore, depression carries the greatest risk for suicide, since most suicide victims were also found to suffer from depression (60%) [6].…”
Section: Introductionmentioning
confidence: 93%
“…Similarly, the prevalence of depression or depressive symptoms among first-year university students in mainland China and Hong Kong was 24.8% and 43.9, respectively ( 3 ) . Although the prevalence of depressive symptoms among college freshmen in these studies differ from that of the general population (37.9% for depressive symptoms) ( 4 ) , which may be due to the use of different measurement tools, different methodologies, and different appraisal standards, previous studies have also found a general increase in mental health problems in college students ( 5 ) . Furthermore, it is well known that depression contributes to the onset of cancer ( 6 ) , diabetes mellitus ( 7 ) , coronary heart disease ( 7 ) , stroke ( 8 ) , and metabolic syndrome ( 9 ) .…”
Section: Introductionmentioning
confidence: 61%